Recessive mutations in EPG5 cause Vici syndrome, a multisystem disorder with defective autophagy - Cullup, Thomas; Kho, Ay L.; Dionisi-Vici, Carlo; Brandmeier, Birgit; Smith, Frances; Urry, Zoe; Simpson, Michael A.; Yau, Shu; Bertini, Enrico; McClelland, Verity; Al-Owain, Mohammed; Kölker, Stefan; et al. (Nature genetics, 2013)
Vici syndrome is a recessively inherited multisystem disorder characterized by callosal agenesis, cataracts, cardiomyopathy, combined immunodeficiency and hypopigmentation. To investigate the molecular basis of Vici syndrome, we carried out exome and Sanger sequence analysis in a cohort of 18 patients. We identified recessive mutations in EPG5 (previously KIAA1632), indicating a causative role in Vici syndrome. EPG5 is the human homologue of the metazoan-specific autophagy gene epg-5, encoding a key autophagy regulator (ectopic P-granules autophagy protein 5) implicated in the formation of autolysosomes. Further studies demonstrated a severe block of autophagosomal clearance in muscle and fibroblasts from EPG5 mutant patients, resulting in autophagic cargo accumulation in autophagosomes. These findings indicate Vici syndrome as a paradigm of a human multisystem disorder associated with defective autophagy, and suggest a fundamental role of the autophagy pathway in the anatomical and functional formation of organs such as the brain, the heart and the immune system.